IMPLEMENTATION OF THE COVID-19 VACCINATION IN THE FRAMEWORK OF MANAGING THE PANDEMIC COVID- 19 - Hariyono Hariyono (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Vaccination is the most effective and efficient public health effort in preventing several dangerous infectious diseases. History has recorded the large role of vaccination in saving the world community from illness, disability and even death due to Vaccination-Preventable Diseases (PD3I). In an effort to overcome the COVID-19 pandemic, COVID-19 vaccination aims to reduce the transmission/transmission of COVID-19, reduce morbidity and mortality due to COVID-19, achieve herd immunity and protect the community from COVID-19 to stay healthy. productive socially and economically. This vaccination activity was carried out on 16-18 February 2022 in the working area of the Cukir Health Center, Jombang Regency. The implementation of Covid-19 vaccination activities is adjusted to the program from the Ministry of Health of the Republic of Indonesia which consists of registration/verification; Screening (anamnesis), physical examination and providing education, as well as approval of action; preparation and administration of the COVID-19 Vaccine; conducting post-COVID-19 Vaccination observations, giving signs of completion of COVID-19 Vaccinations, and issuing COVID-19 Vaccination certificates; recording and inputting data on COVID-19 vaccination results. The results of this vaccination activity were that almost all (88.5%) of the target for dose 1 vaccination in the working area of the Cukir Health Center were students/general public who had exceeded the target of achieving the vaccination implementation and almost all (88.5%) of the target for dose 1 vaccination did not experience any post-immunization follow-up events. . From the results of community service in the working area of the Cukir Public Health Center, it can be concluded that the target of dose 1 vaccination is students/general public and has exceeded the target of achieving the implementation of vaccination, which is 70%. and the target of dose 1 vaccination in the working area of the Cukir Public Health Center did not experience any follow-up events after immunization.